ISOLATION AND SCREENING OF EXOPOLYSACCHARIDES PRODUCING STREPTOCOCCUS THERMOPHILUS STRAINS FOR MANUFACTURE OF INDIGENOUS FERMENTED MILK PRODUCTS - Behare, Pradip Vishnu; BEHARE, PRADIP VISHNU (Indian Journal of Dairy Science, 2015)
Total of seventy eight curd and raw milk samples were collected from different villages and towns of Karnal District, Haryana. The samples were plated on milk agar and 150 mucoid colonies were transferred into skimmed milk. Forty cultures, showing better curdling pattern were subjected to biochemical tests that identified 24 cultures as Streptococcus thermophilus and 16 cultures as Enterococci. S. thermophilus strains were confirmed by molecular methods. Type of exopolysaccharides, either CPS or RPS varied from strain to strain. Six S. thermophilus strains Ram9, Kri2, AM1, MM1, MC1 and Shu3 shown better curdling pattern, acidity, exopolysaccharides production and sensory properties. These cultures can be used for manufacture of indigenous fermented milk products.